PERFORMA SISTEM DETEKSI POTENSI BANJIR BANDANG SAOFFG UNTUK WILAYAH INDONESIA : Studi Kasus Agustus 2020 – Juni 2021 - kiki, kiki (Jurnal Widya Climago, 2022)
Based on BNPB data, floods and flash floods are the most frequent hydrometeorological disasters in Indonesia in the last 5 years. Where the cause of this disaster in general is high intensity (heavy to extreme) rainfall. BMKG has provided early warning products related to heavy rain and potential floods or flash floods for Indonesia region. One of the potential flash flood products is SAOFFG which has been used as an initial guide for flash flood detection. Using the dichotomous verification method, this study calculates 4 verification indices to measure the performance of the SAOFFG system in detecting floods in Indonesia. The result is that the accuracy of this product is quite satisfactory, but the value of False Alarms still tends to be high, which means that this system still predicts flood potential too high compared to observed flood events, especially in several provinces in central and eastern Indonesia.